⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ a × b × c = 1 5 b × c × d = 3 0 c × d × a = 1 0 d × a × b = 6
Given a , b , c , and d are four distinct natural numbers that satisfy the system of equations above.
Determine the value of a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice and easy! *thumbs up
I saw that three equations were a multiple of five, and the only factor those three all had was C so C=5
Then the forth equation had no c, and was not a multiple of five, so the three numbers had to be 1,2,3
1+2+3+5=11
factor LS into 3 ints:
abc = 15 = (1,3,5) bcd = 30 = (nah!) cda = 10 = (1,2,5) dab = 6 = (1,2,3)
it's obvious that 1 appears thrice, and also a, so a=1
bc = 15 bcd = 30
d = 2
cda = 10 cd = 10 c = 5
dab = 6 db = 6 b = 3
a=1, b=3, c=5, d=2 The answer is 1+3+5+2 :D
How...When did you learn that I'am 9 grade in mathematical school and I understand only the half...
Equation 4 : 6=1 2 3 so a, b , d is either of 1,2 or 3. divide eequation 2 by 3 so b/a=3 this gives b=3 , a=1 thus d=2 put values in equation 1 gives c=5. Requires quantities is 11.
Using the first equation
a ∗ b ∗ c = 1 5
we know that a, b, & c must all be factors of 15, so 1, 3, 5, or 15.
Suppose the case where a = 1. If this is true:
1 ∗ b ∗ c = 1 5
b ∗ c = 1 5 .
Then using the 2nd equation
b ∗ c ∗ d = 3 0 , substitute in 1 5 for b ∗ c
1 5 ∗ d = 3 0
d = 2
If d = 2 , then in the 3rd equation:
c ∗ d ∗ a = 1 0 ,
c ∗ 2 ∗ a = 1 0
c ∗ a = 5
Since we assumed a = 1 to start, c = 5 .
Plugging into any equation with b , we arrive at b = 3 .
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ 1 × 3 × 5 = 1 5 3 × 5 × 2 = 3 0 5 × 2 × 1 = 1 0 2 × 1 × 3 = 6
a + b + c + d = 1 + 2 + 3 + 5 = 1 1
I - cxd = 30/b
II - cxdxa = 10 --> a = b/3
III - axbxc = 15 --> (b/3)xbxc = 15 --> c = 45/b^2
IV - dxaxb = 6 --> dx(b/3)xb = 6 --> d = 18/b^2
V - cxdxa = 10 --> (45/b^2)x(18/b^2)x(b/3) = 10 --> 3b^3 = 81 --> b = 3
a = b/3 = 1
c = 45/b^2 = 5
d = 18/b^2 = 2
a + b + c + d = 11
By stating every variable into expressions of b , you'll get the value of b and the rest of the variables. I think it's much faster if you multiply all the given equation, and then divide them.
But really, it's just a matter of opinion of how are you going to approach a certain problem, hehe.
Log in to reply
yeah, you're right! I just showed other way to solve it.
a × b × d = 6 and a × b × c = 1 5 , so a × b must be a factor of both 6 and 15.
1 + 3 + 5 + 2 = 1 1
15 = 1 x 3 x 5; 30 = 1 x 2 x 3 x 5; 10 = 1 x 2 x 5; 6 = 1 x 2 x 3;
so, 1+2+3+5 = 11
I tried a different way and it works. First, look at the last equation,
d a b = 6
Only 3 distinct natural numbers satisfy this equation: 3 , 2 and 1 . From this we know either d , a or b equals 3 , 2 or 1 .
Next, look at the third equation and the last one.
Both of them have d and a . Since both of the equations have an even number on the RHS, we may conclude that d × a = 2 . So, either d or a equals 2 or 1 .
2 × 1 = 2 ---- ( I )
Substitute eqn^ ( I ) into the last equation.
d a b = 6
2 b = 6
b = 3
Substitute eqn^ ( I ) into the third equation.
c d a = 1 0
2 c = 1 0
c = 5
Substitute b = 3 and c = 5 into the second equation.
b c d = 3 0
3 × 5 × d = 3 0
1 5 d = 3 0
d = 2
Since d = 2 , a must equal 1 .
a + b + c + d = 1 + 3 + 5 + 2 = 1 1
I'm not sure how mathematically sound this is, but logically:
Considering the three equations with a,
a b c = 1 5
a c d = 1 0
a b d = 6
a is a common factor on all of the left hand sides of the equations, so the possible values of a are the common factors of the values on the right hand sides of the equations, since a, b, c, and d are all natural numbers. The only common factor of these three numbers (15, 10, and 6) is 1. Therefore, a = 1 .
Considering the three equations with b,
a b c = 1 5
a b d = 6
b c d = 3 0
Likewise, the value of b must be a common factor of the numbers on the right hand sides of the equations. The only such common factor is 3. Therefore, b = 3 .
We know that abc=15, and since a=1 and b=3:
a b c = 1 5
1 ∗ 3 ∗ c = 1 5
3 c = 1 5
c = 5
And finally:
a b d = 6
1 ∗ 3 ∗ d = 6
3 d = 6
d = 2
So the sum of a, b, c, and d:
a + b + c + d = 1 + 3 + 5 + 2 = 1 1
Because we are given that a , b , c , d are 4 natural numbers, the approach of considering common factors works.
However, that is not a necessary assumption for the problem. You should look at the other solutions to understand how to approach this problem.
Problem Loading...
Note Loading...
Set Loading...
If you multiply all the equations together, you get a b c × b c d × c d a × d a b = 1 5 × 3 0 × 1 0 × 6 a 3 b 3 c 3 d 3 = 2 7 0 0 0 a b c d = 3 0 When you divide each equation by this result you get the respective solutions d = 2 a = 1 b = 3 c = 5
Adding these gives a + b + c + d = 1 1